Evaluation of composition suitability of the model for new service development - Skačkauskienė, Ilona; Švogžlys, Povilas (Journal of Business Economics and Management, 2021)
As more and more attention is paid to the formation of models of new service development, it is noticed that the compositions of a new model are usually based only on examples of previous models that were presented in the scientific literature. Although the practical application of the proposed models in any organizational condition is often verified by empirical studies, the revisions of the validity of model compositions are still quite fragmented. The lack of such research does not give the possibility for any further improvement of the model or elimination of the revealed shortcomings and it makes the proper preparation for testing the proposed model in a company complicated. In order to evaluate the suitability of the composition of the newly formed model of service development in the conditions of modern service companies, an empirical evaluation was performed by using the methods of abstraction, comparative analysis, synthesis, and expert survey. According to the results of the research, the suggestions for the improvement of the new service development model were made and guidelines for further research were formulated.